2016
DOI: 10.1016/j.celrep.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Macrolide Antibiotics Leads to Ribosomal Selection against Specific Substrates Based on Their Charge and Size

Abstract: Macrolide antibiotic binding to the ribosome inhibits catalysis of peptide bond formation between specific donor and acceptor substrates. Why particular reactions are problematic for the macrolide-bound ribosome remains unclear. Using comprehensive mutational analysis and biochemical experiments with synthetic substrate analogs, we find that the positive charge of these specific residues and the length of their side chains underlie inefficient peptide bond formation in the macrolide-bound ribosome. Even in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Macrolides, which bind to the nascent peptide exit tunnel, arrest translation at a limited number of codons within the ORF also depending on the nature of the nascent peptide and of the incoming amino acid (27,28,32,38). The context requirements for macrolides, however, are principally different from those for the PTC-targeting antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Macrolides, which bind to the nascent peptide exit tunnel, arrest translation at a limited number of codons within the ORF also depending on the nature of the nascent peptide and of the incoming amino acid (27,28,32,38). The context requirements for macrolides, however, are principally different from those for the PTC-targeting antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, macrolides were considered as general inhibitors of translation by simply obstructing the ribosomal exit tunnel and thereby preventing the progress of the synthesis of the nascent polypeptide chain (Menninger and Otto, 1982;Tenson et al, 2003;Mankin, 2008). In contrast to this view, Mankin and coworkers have demonstrated that the mode of action of these drugs is more complicated (Kannan et al, 2012;Kannan et al, 2014;Sothiselvam et al, 2016). For the majority of proteins, the binding of the drug within the tunnel does cause synthesis to be aborted when the nascent peptide chain reaches a nominal length of 5-11 amino acids where prolongation is prevented, leading to dissociation of the peptidyl-tRNA (drop-off) from the ribosome (Menninger and Otto, 1982;Menninger, 1995;Tenson et al, 2003).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…In the presence of erythromycin, there is stalling during translation of the leader peptide ermCL, which causes the ribosome to block stem-loop formation and exposes the ribosome binding site (RBS) of the downstream cistrons, allowing its expression. (Figure was positive charge of the amino acids occupying the A-and Psites appear to be more important for the efficiency of stalling (Sothiselvam, 2016). Such an allosteric modification of PTC after macrolide binding on the ribosome was presented many years before, when addition of erythromycin in a mixture of ribosomes with bound radioactive chloramphenicol caused complete release of the latter despite the apparent lack of overlap in the binding sites of the two antibiotics (Pestka and LeMahieu, 1974;Dunkle et al, 2010).…”
Section: Figurementioning
confidence: 99%
“…We also want to mention the amino acid modified RNA base puromycin in which the amino acid is attached to the C(3′)‐OH group. This base is in use for ribosomal studies . In our effort to investigate the properties of RNA containing amino acid‐modified nucleosides as units that equip such RNA potentially with peptide‐like properties, we were interested to study the lysine modified uridine base.…”
Section: Introductionmentioning
confidence: 99%